Knowledge, attitude and clinical practice regarding HIV/AIDS among trainee nurses in north-eastern corridor, Ghana - Abdul-Manaf Mutaru; Aminu Ibrahim; Abdul-Nuru Wumpini Osuman; Timothy Atanga Agana; Ahmad Sukerazu Alhassan (Elsevier, 2023)
Background: HIV/AIDS remains a modern-day global burden, killing almost 650,000 people with over 38 million living with the disease, and one and a half million new cases. The risk of infection in clinical practice among health workers has been noted to be high, compared to the general population. Purpose: The study, therefore, sought to determine the knowledge, attitude, and clinical practice regarding HIV/AIDS among nursing students along the north-eastern corridor of Ghana. Methods: A cross-sectional analytical design with a quantitative approach was employed. A multistage stratified random sampling technique was used to select 373 trainee nurses. A Pearson's chi-square analysis was performed at a 0.20 precision level. association between sociodemographic features, knowledge, attitude, and clinical practice were established with a multivariate logistic regression at a 95% confidence level. Results: The majority of participants representing 88.0%, 87.9%, and 57.6% demonstrated satisfactory knowledge, good attitude, and good practices respectively towards HIV/AIDS. Students in their final years of study were 2.3 times more likely to demonstrate good attitudes towards HIV/AIDS than first years (aOR: 2.28; CI: 1.10 - 4.72). Those with sufficient knowledge of HIV/AIDS were 3.5 times more likely to have good attitudes towards its prevention than those with insufficient knowledge levels (aOR: 3.46; 1.76 - 6.77). Conclusion: There are satisfactory knowledge, attitude, and clinical practices among trainee nurses regarding HIV/AIDS in the study setting. Increasing access to knowledge can improve attitudes toward HIV/AIDS. However, there is a need for appraisal of the clinical placement programs of trainee nurses to ensure improved clinical practices. Further studies are needed to ascertain the role of knowledge and attitude in enhanced clinical practices against HIV/AIDS.